PENGARUH VARIASI TEKANAN KEMPA TERHADAP KUAT LENTUR KAYU LAMINASI DARI KAYU MERANTI DAN KERUING - Buan Anshari (Institute of Research and Community Outreach - Petra Christian University, 2006)
The use of timber as a structural material is not only limited to solid timber but also as laminate called glue-laminated timber (glulam). The design of glulam depends on many factors such as the expertise of the designer, timber grade and its combination, adhesive quality, gluing process and clamping process. This research explores the optimum clamp pressure to obtain maximum bending strength of glulam timber which is a combination of Keruing and Meranti Woods using Polivynyl Asetat (PVA) and Melamin Formaldehyde (MF) adhesives. The combination of timber for shear specimen are Keruing Meranti Keruing (KMK), Keruing Keruing Meranti (KKM), and Keruing Meranti Meranti (KMM), the clamp pressures used are 0,2 MPa, 0,6 MPa, 1,0 MPa, and 1,4 Mpa. The duration of clamping is six hours for all combination. The result shows that the bonding strength of shear specimen reaches a maximum of 75,13 kg/cm2 with a clamp pressure of 0,6 MPa using MF adhesive. The maximum flexural strength achieved is 656,37 kg/cm2 with a clamp perssure of 0,6 MPa using MF adhesive as well. Abstract in BahasaIndonesia : Pemakaian kayu sebagai bahan struktural tidak hanya terbatas sebagai kayu utuh, tetapi juga sebagai balok laminasi atau glulam. Proses perancangan kayu dipengaruhi beberapa faktor seperti, tingkat keahlian perancang, faktor kayu yang digunakan beserta kombinasinya, perekat dan proses perekatannya serta proses pengempaannya. Penelitian ini mencari besar tekanan kempa optimum untuk mendapatkan kekuatan lentur maksimum kayu laminasi dari kayu Keruing dan Meranti yang direkatkan dengan perekat Polivynyl Asetat (PVA) dan Melamin Formaldehyde (MF). Kombinasi yang digunakan pada benda uji lamiasi adalah Keruing Meranti Keruing (KMK), Keruing Keruing Meranti (KKM), dan Keruing Meranti Meranti (KMM), dengan tekanan kempa rencana sebesar 0,2 MPa, 0,6 MPa, 1,0 MPa, dan 1,4 MPa untuk semua kombinasi. Proses pengempaan dilakukan selama enam jam. Hasil pengujian pada benda uji kuat lekat menunjukkan keteguhan rekat maksimum sebesar 75,13 kg/cm2 dicapai dengan tekanan kempa 0,6 MPa dengan perekat MF. Sedangkan pada balok laminasi kuat lentur maksimum mencapai 656,37 kg/cm2 pada tekanan kempa 0,6 MPa dengan kombinasi kayu Keruing Meranti Keruing dan perekat MF.